International Accounting and Reporting Issues - 2006 Review - United Nations Conference on Trade; Development (United Nations, 2008)
This volume of the 2006 Review of International Accounting and Reporting Issues contains the proceedings of the twenty-third session of the Intergovernmental Working Group of Experts on International Standards of Accounting and Reporting. The two main agenda items the session dealt with were: a review of practical implementation issues of International Financial Reporting Standards; and comparability and relevance of existing indicators on corporate responsibility.